Five-year clinical performance of the dentine Deproteinization Technique in non-carious cervical lesions - Games Torres, Carlos Rocha [UNESP]; Barcellos, Daphne Camara [UNESP]; Batista, Graziela Ribeiro [UNESP]; Pucci, Cesar Rogerio [UNESP]; Sala Antunes, Maria Julia [UNESP]; la Cruz, Daniela Barone de [UNESP]; Borges, Alessandra Buehler [UNESP] (Elsevier B.V., 2014)
Objective: The aim of this study was to evaluate the 5-year clinical performance of composite restorations of non-carious cervical lesions (NCCL) using a total-etch adhesive system with or without collagen removal with 10% sodium hypochlorite (NaOCl).Methods: In this study randomized controlled split-mouth clinical trial, one-hundred and thirty-eight NCCL were restored into 30 patients. Each patient received at least one pair of composite restorations (Filtek A110/3M ESPE), bonded either with 2 techniques: Conventional Technique - acid etching with 37% phosphoric acid + Prime & Bond NT (Denstply DeTrey); Deproteinization Technique - acid etching with 37% phosphoric acid + 10% NaOCl for 1 min + Prime & Bond NT. The two techniques were evaluated using the United States Public Health Service (USPHS) criteria at baseline, 18 months, 3 and 5 years. After five years, one-hundred and six restorations were evaluated in 24 patients. Data were analyzed using the Chi-Square test (p < 0.05).Results: There were no statistically significant differences between the two techniques regarding the evaluated parameters (p > 0.05).Conclusion: After 5 years, the application of 10% NaOCl deproteinization on etched dentine did not affect the clinical performance of composite restorations placed in NCCL when compared to the conventional total-etch technique.Clinical significance: Clinical studies evaluating the performance of the Deproteinization Technique are scarce. In this study, this technique showed similar clinical performance at the end of 5 years when compared to a conventional total-etch technique. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Clinical; Adhesive systems; Collagen, Sodium hypochlorite; Composite